Identification of Acinetobacter seifertii isolated from Bolivian hospitals - Cerezales, Mónica; Xanthopoulou, Kyriaki; Ertel, Julia; Nemec, Alexandr; Bustamante, Zulema; Seifert, Harald; Gallego, Lucia; Higgins, Paul G (Journal of Medical Microbiology, 2018)
Acinetobacter seifertii is a recently described species that belongs to the Acinetobacter calcoaceticus-Acinetobacter baumannii complex. It has been recovered from clinical samples and is sometimes associated with antimicrobial resistance determinants. We present here the case of three A. seifertii clinical isolates which were initially identified as Acinetobacter sp. by phenotypic methods but no identification at the species level was achieved using semi-automated identification methods. The isolates were further analysed by whole genome sequencing and identified as A. seifertii. Due to the fact that A. seifertii has been isolated from serious infections such as respiratory tract and bloodstream infections, we emphasize the importance of correctly identifying isolates of the genus Acinetobacter at the species level to gain a deeper knowledge of their prevalence and clinical impact.
Keywords: katétrové infekce; polymerázová řetězová reakce; Bolívie; High-Throughput Nucleotide Sequencing; RNA, Ribosomal, 16S; antibakteriální látky; Genome, Bacterial; Acinetobacter baumannii; Acinetobacter; Acinetobacter Infections; genom bakteriální; DNA Gyrase; DNA, Bacterial; DNA bakterií; lidé; Catheter-Related Infections; Anti-Bacterial Agents; Humans; vysoce účinné nukleotidové sekvenování; infekce bakteriemi rodu Acinetobacter; spektrometrie hmotnostní - ionizace laserem za účasti matrice; DNA gyráza; RNA ribozomální 16S; Polymerase Chain Reaction; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Bolivia